Sodium intake, brain c-Fos protein and gastric emptying in cell-dehydrated rats treated with methysergide into the lateral parabrachial nucleus - David, Richard B. [UNESP]; Roncari, Camila F. [UNESP]; Lauar, Mariana R. [UNESP]; Vendramini, Regina C. [UNESP]; Antunes-Rodrigues, José; Menani, José V. [UNESP]; Luca, Laurival A. de [UNESP] (Elsevier B. V., 2015)
Previous studies from our laboratory have shown that methysergide, a serotonergic antagonist, injected into the lateral parabrachial nucleus (LPBN) combined with a pre-load of 2 M NaCl, given by gavage, induces 0.3 M NaCl intake. The mechanisms involved in this paradoxical behavior are still unknown. In the present work, we investigated the effect of serotonergic blockade into the LPBN on hindbrain and hypothalamic activity, gastric emptying and arterial blood pressure in cell-dehydrated rats. Methysergide plus 2 M NaCl infused intragastrically or intravenously promoted 0.3 M NaCl intake in two-bottle tests. In cell-dehydrated rats with no access to fluids, methysergide compared to vehicle increased Fos immunoreactivity in the medial nucleus of the solitary tract, area postrema and non-oxytocinergic cells of the ventral portion of the hypothalamic paraventricular nucleus (PVN). There was no alteration in the number of neurons double-labeled for Fos-ir and oxytocin in the PVN and supraoptic nuclei. There was also no alteration in plasma oxytocin and vasopressin, or arterial pressure. In rats cell-dehydrated by i.v. 2 M NaCl, methysergide also did not change the amount of an intragastric load of 0.3 M NaCl retained in the stomach or intestine. The results suggest that methysergide injected into the LPBN of cell-dehydrated rat does not alter primary inhibitory signals that control sodium intake. The inhibitory signals blocked by methysergide in the LPBN possibly originated from activation of brain osmoreceptors, second order visceral/hormonal signals or a combination of both.
Keywords: Dehydration; Medulla oblongata; Neurohypophysis; Satiety; Sodium appetite; Thirst